Evaluation of Physical Capacity Balance in Older Adults - Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo; Ernesto Julio Bernal Valladares; Alexis Sebastián García Somodevilla; Fernando Jesús del Sol Santiago (Revista Finlay)
Foundation: alterations in gait and balance in the elderly are the main cause of falls. Valid and reliable valuation methods are necessary to identify the risk of falls. Objective: to determine the relationships between some indicators of the Fullerton advanced equilibrium scale test and age in older adults. Methods: a descriptive cross sectional exploratory study was conducted between September and December 2017 in elder Day Care Centers of the Combined Sports Center N0 5 of the Cienfuegos Municipality. For this, 115 elderly adults were selected. The general variables were: age and sex. Four of the ten items that make up the Fullerton test were taken. The Spearman correlation coefficient and the Gamma coefficient were applied, with 95 % confidence. The results were exposed through the use of tables. Results: the most represented age group was 71-75 years (40.9 %), with a prevalence of males (16 %). In the application of the Fullerton test older adults managed to maintain balance in standing, in more than 25 % of cases, could take the object either without moving the feet or by a step, in the orthostatic control the highest values they are concentrated in the group of 71-75 years (40 %). Conclusions: older adults who managed to maintain balance in standing with their eyes closed, could either take the object without moving the feet or through a step with supervision, in the orthostatic control the highest values are concentrated in the group of 71-75 years.